The Impact of Financial Liberalization on Islamic Bank's Efficiency in Indonesia - Wiwiek Rabiatul Adawiyah (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
The aim of this research is analyze the state of efficiency demonstrated by foreign banks, as aggressor, as compared to that of the local banks – government banks and Islamic banks during the period 2009-2012. Data Envelopment Analysis (DEA) with intermediation approach is used as the main tool of analysis. Input variable chosen are deposit, asset, and personnel expenses. Meanwhile loan and income are chosen as output variable. To find out the difference of efficiency between foreign banks and islamic banks, this study use parametric different test of Independent Sample T-test. The study indicates that foreign banks are less efficient if compared to the local banks, especially Islamic banks and Sharia Business Units. It is also evidenced that there is no significant difference between the efficiency of foreign and Islamic banks during the period 2009-2012.DOI: 10.15408/aiq.v7i2.1680